Preparation for Trial - Milton D. Green (Washington University Law Quarterly, 1955)
It is often said that trials are won in the office and not in the courtroom. We are told that a case well prepared is half-won. These, and similar statements, are truisms, but because of their vague generality they do not help us much in going about the actual business of preparation. In order to be really helpful, any discussion of preparation for trial must get down to practical, specific details. I am going to try to be specific and I am going to try to cover, at least in outline, the steps which a lawyer must take in order to be adequately prepared for trial. In doing so it may sometimes be necessary to labor the obvious, and for this I apologize in advance. But in justification may I remind you that neglect of the obvious is frequently one of the causes of disaster.
Keywords: Trial practice